The Interactions between the Business Strategies and Financial Strategies among the MNCs in Singapore - Lim, Kenneth See Khoon (2008)
MNCs have been playing an overwhelming role in Singapore's economic development. Large Singapore MNCs tend to be more westernized. Although cultural differences exist, Singapore is open and pragmatic, and therefore permits Western practices to be introduced and become the preferred management style.